Genetic and microbial factors modulating the ubiquitin proteasome system in inflammatory bowel disease. Issue 8 (3rd October 2013) - Cleynen, Isabelle; Vazeille, Emilie; Artieda, Marta; Verspaget, Hein W; Szczypiorska, Magdalena; Bringer, Marie-Agnès; Lakatos, Peter L; Seibold, Frank; Parnell, Kirstie; Weersma, Rinse K; Mahachie John, Jestinah M; Morgan-Walsh, Rebecca; et al.
Abstract : Objective: Altered microbiota composition, changes in immune responses and impaired intestinal barrier functions are observed in IBD. Most of these features are controlled by proteases and their inhibitors to maintain gut homeostasis. Unrestrained or excessive proteolysis can lead to pathological gastrointestinal conditions. The aim was to validate the identified protease IBD candidates from a previously performed systematic review through a genetic association study and functional follow-up. Design: We performed a genetic association study in a large multicentre cohort of patients with Crohn's disease (CD) and UC from five European IBD referral centres in a total of 2320 CD patients, 2112 UC patients and 1796 healthy controls. Subsequently, we did an extensive functional assessment of the candidate genes to explore their causality in IBD pathogenesis. Results: Ten single nucleotide polymorphisms (SNPs) in four genes were significantly associated with CD: CYLD, USP40, APEH and USP3. CYLD was the most significant gene with the intronically located rs12324931 the strongest associated SNP (pFDR =1.74e-17, OR=2.24 (1.83 to 2.74)). Five SNPs in four genes were significantly associated with UC: USP40, APEH, DAG1 and USP3. CYLD, as well as some of the other associated genes, is part of the ubiquitin proteasome system (UPS). We therefore determined if the IBD-associated adherent-invasive Escherichia coli (AIEC) can modulate the UPS functioning. Infection of intestinal epithelial cells with the AIEC LF82 reference strain modulated the UPS turnover by reducing poly-ubiquitin conjugate accumulation, increasing 26S proteasome activities and decreasing protein levels of the NF-κB regulator CYLD. This resulted in IκB-α degradation and NF-κB activation. This activity was very important for the pathogenicity of AIEC since decreased CYLD resulted in increased ability of AIEC LF82 to replicate intracellularly. Conclusions: Our results reveal the UPS, and CYLD specifically, as an important contributor to IBD pathogenesis, which is favoured by both genetic and microbial factors.